Proceedings of the 2016 3rd International Conference on Materials Engineering, Manufacturing Technology and Control 2016
DOI: 10.2991/icmemtc-16.2016.148
|View full text |Cite
|
Sign up to set email alerts
|

Review of recent research in nano cellulose preparation and application from jute fibers

Abstract: Abstract. Jute is the second most important fiber in the world, which is easy to grow on all types of soil from clay to sandy loam. The popularity of jute is attributable to its abundant and cheapness, and jute fiber is mainly used in the manufacture of coarse fabrics like bags, hessian, sacking, canvas and twines. Jute is rich in cellulose, which could be served as promising candidates for nano materials production. Nano cellulose features concerned its high strength and stiffness, renewability, low density, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…[4][5][6][7] Nanocellulose is typically in the shape of nanowhiskers or rods with a high aspect ratio (3-5 nm wide, 50-500 nm length) and is highly crystalline (60-90%). 8,9 Nanocellulose has emerged as a natural source for groundbreaking applications in materials science [10][11][12] and has demonstrated uses in diverse elds, including adsorbents for environmental remediation, 13 as hydrogels and aerogels, 14 as a suitable substrate for surface enhanced Raman scattering (SERS) studies, 15 for chemical and surface modications on the cellulosic backbone, 16,17 as composite inks for 3D bioprinting, 18 as an iridescent chiral nematic material, 19 and several applications in biomedicine. [20][21][22][23][24] During sulfuric acid hydrolysis of cellulose, the protic acid catalyzes the cleavage of a chemical bond by a nucleophilic substitution reaction 7 with sulfate groups (R-OSO 3 À ) forming on the nanocellulose surface; 25 cleavage occur along the amorphous regions of the cellulose and upon sonication crystalline rod-like nanocellulose whiskers form.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Nanocellulose is typically in the shape of nanowhiskers or rods with a high aspect ratio (3-5 nm wide, 50-500 nm length) and is highly crystalline (60-90%). 8,9 Nanocellulose has emerged as a natural source for groundbreaking applications in materials science [10][11][12] and has demonstrated uses in diverse elds, including adsorbents for environmental remediation, 13 as hydrogels and aerogels, 14 as a suitable substrate for surface enhanced Raman scattering (SERS) studies, 15 for chemical and surface modications on the cellulosic backbone, 16,17 as composite inks for 3D bioprinting, 18 as an iridescent chiral nematic material, 19 and several applications in biomedicine. [20][21][22][23][24] During sulfuric acid hydrolysis of cellulose, the protic acid catalyzes the cleavage of a chemical bond by a nucleophilic substitution reaction 7 with sulfate groups (R-OSO 3 À ) forming on the nanocellulose surface; 25 cleavage occur along the amorphous regions of the cellulose and upon sonication crystalline rod-like nanocellulose whiskers form.…”
Section: Introductionmentioning
confidence: 99%
“…When the reaction time increases more than 20 min, the mass transfer resistance gradually decreases and the specific surface of the grass wastes increases with reaction time increament owing to the breakdown of their net structure and even the enlargement of the interand intra-fiber pores, which results from the hydrolysis of more and more cellulose that leading to the decrement of GNFC Yield with reaction time increment, [ 6 ]. The yield decreased with time increment than 20 min, therefore, the optimum yield value for obtaining cellulose from NaClO/GNFC was 95% which is higher compared to the cellulose yield of NaOH/GNFC of the previous publications which was 89% of pineapple [ 41 ], 83.40% of blenched fiber [ 42 ], 67.40% for non-woody biomass constitutes [ 34 ], 85.40% for non-woody biomass constitutes, 54.30% for organo-solvent miscanthus pulp (OMP) [ 31 ], and 81.00% and 54.00% from flax fibers and cotton linters [ 29 ]. Moreover, the yield of NaClO/H 2 SO 4 cellulose was 90.00% the yield of the previous investigators which was 82% for non-woody biomass constitutes [ 43 ], ranging between 55 and 60% for bleached kraft pulp of loblolly pinewood [ 44 ], 85.75% for filter paper [ 6 ], 83.60% for native cellulosic feedstock [ 45 ] ( Apendix A ), 84.00% for oil palm ( Elaeisguineensis ) empty fruit bunch [ 46 ], from flax fibers (81.00%) and 54% from flax fibers (81.00%) and cotton linters [ 14 ].…”
Section: Resultsmentioning
confidence: 94%
“…Yahya et al [ 28 ] found that oil palm ( Elaeisguineensis ) empty fruit bunch (OPEFB) has nanocellulose yield of 81.37%. Duan and Yu [ 29 ] concluded that the jute fibers nanocellulose has high yield of 80%. Ma et al [ 30 ] extracted nanocellulose from Xanthoceras sorbifolia husks through a series of chemical treatments, after which the obtained nanocellulose had a rod-like shape and diameter of 38 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In view of environmental concern, the synthetic fibre polymer composite materials are not eco-friendly and non-biodegradable. However, when natural fibre is introduced in the field as a replacement for synthetic fibre, many studies have reported that natural fibre-reinforced polymer composite sustainability is high [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Its acceptability to the environment is better due to renewability and biodegradability.…”
Section: Introductionmentioning
confidence: 99%